Paracrine stimulation of perinatal lung functional and structural maturation by mesenchymal stem cells - Janine Obendorf; Claire Fabian; Ulrich H. Thome; Mandy Laube (Stem Cell Research & Therapy, 2020)
Abstract Background Mesenchymal stem cells (MSCs) were shown to harbor therapeutic potential in models of respiratory diseases, such as bronchopulmonary dysplasia (BPD), the most common sequel of preterm birth. In these studies, cells or animals were challenged with hyperoxia or other injury-inducing agents. However, little is known about the effect of MSCs on immature fetal lungs and whether MSCs are able to improve lung maturity, which may alleviate lung developmental arrest in BPD. Methods We aimed to determine if the conditioned medium (CM) of MSCs stimulates functional and structural lung maturation. As a measure of functional maturation, Na+ transport in primary fetal distal lung epithelial cells (FDLE) was studied in Ussing chambers. Na+ transporter and surfactant protein mRNA expression was determined by qRT-PCR. Structural maturation was assessed by microscopy in fetal rat lung explants. Results MSC-CM strongly increased the activity of the epithelial Na+ channel (ENaC) and the Na,K-ATPase as well as their mRNA expression. Branching and growth of fetal lung explants and surfactant protein mRNA expression were enhanced by MSC-CM. Epithelial integrity and metabolic activity of FDLE cells were not influenced by MSC-CM. Since MSC’s actions are mainly attributed to paracrine signaling, prominent lung growth factors were blocked. None of the tested growth factors (VEGF, BMP, PDGF, EGF, TGF-β, FGF, HGF) contributed to the MSC-induced increase of Na+ transport. In contrast, inhibition of PI3-K/AKT and Rac1 signaling reduced MSC-CM efficacy, suggesting an involvement of these pathways in the MSC-CM-induced Na+ transport. Conclusion The results demonstrate that MSC-CM strongly stimulated functional and structural maturation of the fetal lungs. These effects were at least partially mediated by the PI3-K/AKT and Rac1 signaling pathway. Thus, MSCs not only repair a deleterious tissue environment, but also target lung cellular immaturity itself.